Development of a Modern Urban Quarter through the Example of Western European Cities - Dagdanova, Irina; Alsagaeva, Irina (проект байкал, 2016)
The article presents realizations of new types of urban quarters and present-day reconstructions of these urban units aimed to achieve the higher quality of life of the population.